Endophytic Fungi from Simpei Fern Rhizomes and Its Phosphate Solubilization Activity - Nopitasari, Windi; Handayani, Dezi; Advinda, Linda; Irdawati, Irdawati (Jurnal Serambi Biologi, 2023)
Phosphate is very abundant in the soil, but only a small amount was dissolved. Some fungi have the ability to dissolve phosphates. This fungi is expected to overcome the excessive use of phosphate fertilizers. Those fungi ussualy found in soil or rhizorfere and sometimes they are endophytic. Rhizome of the simpei fern has endophytic fungi and its phosphate solubilizing activity was not known yet. This study aims to isolate endophytic fungi from rhizome of the simpei fern and to determine its phosphate solubilizing activity. Samples of simpei fern rhizome were taken from Nagari Aka Barayun, Harau District, Lima Puluh Kota District, West Sumatra. Surface sterilization using 0.5% NaOCL. The isolation medium for endophytic fungi used PDA medium and the phosphate solvent activity test used Pikovskaya medium. Six isolates of endophytic fungi were successfully isolated from the rhizome of the simpei fern and only three isolates were able to dissolve phosphate. The isolates are isolates R4, R5, and R6. Phosphate solubilizing activity of isolate R5 was higher than other isolates, although all isolates had a low phosphate solubility index.